Preparation method of antibacterial film

By modifying and coating the surface of mesoporous silica and sodium hyaluronate-catechol compounds, an enzyme-responsive intelligent antibacterial membrane was prepared, which solved the problem of uncontrollable release of silver ions in silver-based antibacterial membrane materials, and achieved targeted targets The selective release and long-term stability of microorganisms are suitable for food processing and biomedicine fields.

CN119215675APending Publication Date: 2024-12-31JIANGSU UNIV OF TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411379097.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing silver-based antibacterial membrane materials have the problem of uncontrollable continuous release of silver ions, which leads to toxic side effects and waste of resources on the water environment. At the same time, it cannot selectively retain beneficial microorganisms such as probiotics, which limits its inability to food processing, biomedicine and other fields. Widely used.

Method used

Using the preparation method of enzyme-responsive intelligent antibacterial membrane, nanosilver is fixed by thiolation modification and sulfonation on the mesoporous silica surface, and coated with sodium hyaluronate-catechol compound to form m-SiO2 -SH-Ag-HA composite material ensures stable and sustained release of silver ions.

Benefits of technology

It effectively avoids the uncontrolled release of silver ions, extends the service life of the membrane, reduces the cytotoxicity to non-targeted bacteria and mammalian cells, achieves the selective release of target microorganisms, and avoids environmental toxicity side effects and waste of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215675A_ABST
    Figure CN119215675A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an antibacterial film. The preparation method comprises the following steps: preparing and forming an m-SiO2-SH-Ag-HA composite material; and blending the m-SiO2-SH-Ag-HA composite material into a membrane material, so as to form the antibacterial membrane. The hydrophilic HA in the antibacterial film formed by the preparation method can coat the outer side of m-SiO2-SH-Ag through electrostatic interaction to form an electrostatic barrier, effectively prevent the release of Ag < + > and play roles in stabilization, protection and slow release on one hand, and can increase the hydrophilicity of the surface of the film and effectively inhibit the early adhesion of bacteria on the other hand. When the target bacteria appear, HA coated on the surface of the m-SiO2-SH-Ag-HA is degraded by secreting hyaluronidase, so that the exposure and release of Ag < + > are promoted. The antibacterial film disclosed by the invention can release sterilization components through enzymatic initiation to realize on-demand antibiosis, and toxic and side effects and resource waste caused by uncontrollable continuous release of Ag < + > to the environment are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing an antibacterial film, and further to a method for preparing an enzyme-responsive intelligent antibacterial film. Background Art

[0002] Membrane separation technology is widely used in water treatment, food processing, pharmaceutical production and other fields due to its excellent filtration and retention performance. However, "membrane pollution" is still the most serious challenge it faces in practical applications. According to the type of pollutants, "membrane pollution" can be divided into organic pollution, inorganic pollution and biological pollution. Among them, biological pollution caused by the attachment, growth and reproduction of microbial cells or flocs on the membrane surface and in the membrane pores is considered to be the most harmful membrane pollution.

[0003] As an excellent broad-spectrum antibacterial agent, nanosilver has been widely used in the preparation of anti-fouling membrane materials. The existing technology introduces silver-based antibacterial agents into membrane materials by means of blending, grafting, loading, etc. Nanosilver can release silver ions in water media, which have a toxic effect on cell membranes and enzyme systems, leading to enzyme inactivation and the generation of reactive oxygen species (ROS) to achieve antibacterial effects. In addition, the physical contact between nanoparticles and microorganisms can also change the properties of cell membranes, destroy the microbial structure, and reduce the adhesion, growth and biofilm formation of bacteria on the membrane surface and in the pores, so that the nanocomposite membrane material has good anti-biological pollution performance, thereby extending the service life of the membrane material. However, the current silver-based antibacterial membrane materials all have the problem of "uncontrollable and continuous release of silver ions", and their "permanent release state" is bound to cause certain toxic side effects and waste of resources to organisms in the water environment. When the silver ions are released, their antibacterial properties will also be greatly reduced. In addition, with the application of membrane separation technology in food processing, biomedicine, aquaculture and other fields, the applicant found that not all industries need to be completely sterile. On the contrary, some harmless microorganisms (such as probiotics, etc.) need to be retained in specific application environments. However, traditional antibacterial membranes have no selectivity for target microorganisms during use, which has become a major problem limiting the widespread application of this method. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent, and proposes a method for preparing an enzyme-responsive intelligent antibacterial film, comprising:

[0005] A method for preparing an antibacterial film, comprising:

[0006] Preparation of m-SiO 2 -SH-Ag-HA composites;

[0007] The m-SiO 2-SH-Ag-HA composite material is blended into the membrane material to form the antibacterial film.

[0008] The m-SiO 2 Mesoporous silica is the abbreviation of mesoporous silicon dioxide. Mesoporous silica is an ideal carrier for preparing functional materials because of its large specific surface area, regular and adjustable pore structure, good hydrothermal stability, and the ability to complete a series of physical and chemical processes such as adsorption, modification, and separation in the pores. For mesoporous silicon-based materials, the larger the specific surface area, the larger the surface functionalization space that can be applied, and the more sites that the material can bind to. By modifying the surface of mesoporous silica with thiol, -SH can be grafted on its inner and outer surfaces, and further sulfonated to increase the number of negative charges it carries, and use electrostatic effects to adsorb Ag. + , firmly fix it on the entire surface of mesoporous silica, and ensure that nano-Ag is densely, stably and evenly dispersed in the pores and on the surface. At the same time, the surface of mesoporous silica has a large number of silanols and siloxanes, which makes m-SiO 2 -SH-Ag composite materials can bind more tightly with sodium hyaluronate-catechol (HA) compounds, greatly reducing the uncontrolled release of silver ions and increasing the service life of the antibacterial film.

[0009] HA is a hyaluronic acid-sodium catechol compound. In the present invention, the hydrophilic HA can be coated on the m-SiO 2 -SH-Ag outside, forming an electrostatic barrier, effectively preventing Ag + The release of HA plays a role of stabilization, protection and slow release. On the one hand, it can increase the hydrophilicity of the membrane surface and effectively inhibit the early adhesion of bacteria. Since HA has high biocompatibility and carries a negative charge in aqueous solution, m-SiO 2 -SH-Ag-HA has low cytotoxicity to non-target bacteria and mammalian cells. When the target bacteria appear, they secrete hyaluronidase to convert m-SiO 2 The HA coated on the surface of -SH-Ag-HA degrades to produce positively charged m-SiO 2 -SH-Ag + , while combining with bacteria through electrostatic interaction, promoting Ag + The antibacterial film of the present invention can release the antibacterial agent triggered by the intelligent enzyme on demand when the target microorganism appears, avoiding Ag + Uncontrolled continuous release causes toxic side effects to the environment and waste of resources.

[0010] In some cases, the preparation forms m-SiO 2 -SH-Ag-HA composite material, comprising:

[0011] The sulfonated m-SiO 2 -SH is dispersed in water to form m-SiO 2 -SH solution, in the m-SiO 2 Add AgNO 3 The solutions are mixed to form a first mixed solution, and the first mixed solution is centrifuged and washed to obtain m-SiO 2 -SH-Ag solid; the m-SiO 2 -SH-Ag solid is dispersed in water, and sodium hyaluronate-catechol (HA) compound is added to form a second mixed solution, and the second mixed solution is stirred at room temperature and dark conditions, and then centrifuged, washed and dried to form m-SiO 2 -Ag-HA composite material.

[0012] In some cases, the m-SiO 2 Add AgNO 3 The solutions are mixed to form a first mixed solution, including, in the m-SiO 2 Add AgNO 3 The solutions are mixed and magnetically stirred in the dark for a first preset time to form the first mixed solution.

[0013] In some cases, the preparation method of the sodium hyaluronate-catechol (HA) compound includes: adding sodium hyaluronate, 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and NHS (N-hydroxysuccinimide) to PBS, stirring for 1 hour, supplementing dopamine, and continuing the reaction overnight. The product is dialyzed and freeze-dried to obtain the sodium hyaluronate-catechol (HA) compound.

[0014] In some cases, the thiol-modified mesoporous silica m-SiO 2 The preparation method of m-SiO-SH comprises: adding CTAB (hexadecyltrimethylammonium bromide) to a sodium hydroxide solution, heating and stirring to 80°C, then adding 3 mL of tetraethyl orthosilicate, stirring for 2 hours, standing and aging for 3 hours, and then washing and drying; refluxing the dried powder in 150 mL of ethanol and 2 mL of hydrochloric acid for 12 hours, washing and drying to obtain the m-SiO 2 . The powder m-SiO 2 Ultrasonic dispersion in ethanol solution, add 3-mercaptopropyltrimethoxysilane, reflux at 70°C for 12h under magnetic stirrer. After cooling, wash repeatedly with ethanol and deionized water, and dry and grind at 60°C.

[0015] In some cases, the thiol-modified mesoporous silica (m-SiO 2-SH) sulfonation treatment process includes: m-SiO 2 -SH powder was dispersed in chlorosulfonic acid (ClSO 3 H, 0.1 mol / L) solution, stirred magnetically at room temperature for 24 hours, washed repeatedly with ethanol and deionized water, dried at 60°C and ground into powder.

[0016] In some cases, the m-SiO 2 -SH-Ag-HA composite material is blended into the membrane material to form the antibacterial membrane, comprising:

[0017] m-SiO 2 -SH-Ag-HA composite material is added to an organic solvent and stirred to make it evenly dispersed, and then a preset amount of base film material is added to form a second mixed liquid, the second mixed liquid is placed in an oven and heated to 50-80°C to dissolve, and the second mixed liquid after heating and dissolving is placed on a magnetic stirrer and stirred overnight; the stirred second mixed liquid is placed in an oven and allowed to stand for 24 hours to obtain a casting liquid, the casting liquid is naturally allowed to stand and wait for it to cool to room temperature, the cooled casting liquid is poured on a non-woven fabric, and it is evenly scraped with a glass rod, and then the glass plate covered with the non-woven fabric is immersed in a gel bath, and it is solidified to form a film of uniform thickness, and the film is continuously immersed for 24 hours to complete the phase conversion to obtain the antibacterial film.

[0018] In some cases, the gel bath is one or more of pure water, 5%-10% propanol solution, and 2%-10% ethanol solution.

[0019] In some cases, the base membrane material is one or more of polyethersulfone, polysulfone, polyvinylidene fluoride, cellulose acetate, polyamide, and chitosan.

[0020] According to the embodiments of the present invention, the technical effects of the present application are at least as follows:

[0021] The surface of mesoporous silica can be modified by thiolation and sulfonation to enhance the Ag + The interaction between HA and -SH firmly fixes it on the inner and outer surfaces of mesoporous silica, ensuring that nano-Ag is densely, stably and evenly dispersed in the pores and on the surface, while effectively regulating the concentration and distribution of silver ions on the inner and outer surfaces of mesoporous silica. 2 -SH-Ag outside, forming an electrostatic barrier, effectively preventing Ag + The excessive release of HA plays a role of stabilization, protection and slow release. On the one hand, it can increase the hydrophilicity of the membrane surface and effectively inhibit the early adhesion of bacteria. Since HA has high biocompatibility and carries a negative charge in aqueous solution, m-SiO 2-SH-Ag-HA has low cytotoxicity to non-target bacteria and mammalian cells. When the target bacteria appear, they secrete hyaluronidase to convert m-SiO 2 The HA coated on the surface of -SH-Ag-HA degrades to produce positively charged m-SiO 2 -SH-Ag + , while combining with bacteria through electrostatic interaction, promoting Ag + The HA coating enables the intelligent enzyme-triggered antimicrobial agent to be released on demand when the target microorganism appears, avoiding Ag + The uncontrollable continuous release causes toxic side effects and waste of resources to the environment, effectively extending the service life of the antibacterial film. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0023] Figure 1 To add different contents of m-SiO 2 -Surface contact angle of SH-Ag-HA composite film material;

[0024] Figure 2 m-SiO 2 Ag-SH-Ag-HA composites under different conditions + Schematic diagram of release behavior;

[0025] Figure 3 To add m-SiO 2 -SH-Ag-HA composite PES membrane in different filtration media + Schematic diagram of release behavior;

[0026] Figure 4 m-SiO 2 -Transmission electron microscopy image of SH-Ag-HA. DETAILED DESCRIPTION

[0027] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0028] A method for preparing an antibacterial film, comprising:

[0029] Preparation of m-SiO 2 -SH-Ag-HA composites;

[0030] m-SiO 2 -SH-Ag-HA composite material is blended into the membrane material to form the antibacterial film.

[0031] In some embodiments, the m-SiO 2 The process of SH-Ag-HA composite material includes: sulfonated m-SiO 2 -SH is dispersed in water to form m-SiO 2 -SH solution, in the m-SiO 2 Add AgNO 3 The solutions are mixed to form a first mixed solution, and the first mixed solution is centrifuged and washed to obtain m-SiO 2 -SH-Ag solid; the m-SiO 2 -SH-Ag solid is dispersed in water, and sodium hyaluronate-catechol (HA) compound is added to form a second mixed solution, and the second mixed solution is stirred at room temperature and dark conditions, and then centrifuged, washed and dried to form m-SiO 2 -Ag-HA composites. 3 H, 0.1 mol / L) solution to sulfonate the mesoporous silica material can significantly increase the number of negative charges it carries, thereby increasing the Ag + The interaction between the sodium hyaluronate and thiol-SH makes it firmly loaded on the pores and internal and external surfaces of mesoporous silica. Sodium hyaluronate is the sodium salt form of hyaluronic acid. It has stronger tissue penetration ability due to its sodium stability. Catechol has obvious antioxidant and antibacterial effects. Sodium hyaluronate-catechol (HA) compound is used to treat m-SiO 2 -SH-Ag is coated and further blended into the membrane material, which can also improve the antibacterial and antioxidant properties of the membrane material during long-term use.

[0032] In some embodiments, the sulfonated m-SiO 2 Add AgNO 3 The solutions are mixed to form a first mixed solution, including, in the sulfonated m-SiO 2 Add AgNO 3 The solutions are mixed and magnetically stirred in the dark for a certain period of time to form the first mixed solution. Dark conditions can effectively avoid Ag + Photoreduction, magnetic stirring can make Ag + It combines with -SH groups more quickly and evenly, extending the service life of the antibacterial material.

[0033] In some embodiments, the preparation method of the sodium hyaluronate-catechol (HA) compound comprises: adding sodium hyaluronate, 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and NHS (N-hydroxysuccinimide) to PBS, stirring for 1 hour, adding dopamine, reacting overnight, and dialyzing and freeze-drying the product to obtain the sodium hyaluronate-catechol (HA) compound. The ortho-hydroxyl group in catechol reacts with Ag. + There is a strong chelating effect between them. Sodium hyaluronate-catechol (HA) compound is used to chelate m-SiO 2 -SH-Ag coating can also increase the firmness of the coating layer and play a role in sustained release of antibacterial agents.

[0034] In some embodiments, the thiol-modified mesoporous silica (m-SiO 2 The preparation method of m-SiO-SH comprises: adding CTAB (hexadecyltrimethylammonium bromide) to a sodium hydroxide solution, heating and stirring to 80°C, then adding 3 mL of tetraethyl orthosilicate, stirring for 2 hours, standing and aging for 3 hours, and then washing and drying; refluxing the dried powder in 150 mL of ethanol and 2 mL of hydrochloric acid for 12 hours, washing and drying to obtain the m-SiO 2 1g of powdered m-SiO 2 Ultrasonic dispersion was performed in 200 mL of ethanol solution, and 2 mL of 3-mercaptopropyltrimethoxysilane was added, and refluxed at 70 °C for 12 h under a magnetic stirrer. After cooling, the mixture was repeatedly washed with ethanol and deionized water, and dried and ground at 60 °C.

[0035] In some embodiments, the m-SiO 2 -SH-Ag-HA composite material is blended into the membrane material to form the antibacterial membrane, comprising:

[0036] m-SiO 2 -SH-Ag-HA composite material is added to an organic solvent and stirred to make it dispersed evenly, and then a preset amount of base film material is added to form a second mixed solution, the second mixed solution is placed in an oven at 50-80°C to heat and dissolve, and the heated and dissolved second mixed solution is placed on a magnetic stirrer and stirred overnight; the stirred second mixed solution is placed in an oven and allowed to stand for 24 hours to obtain a casting solution, the casting solution is naturally placed to cool to room temperature, the cooled casting solution is poured on a non-woven fabric, and is evenly scraped with a glass rod, and then the glass plate covered with the non-woven fabric is immersed in a gel bath, and it is solidified to form a uniform film, and the film is continuously immersed for 24 hours to complete the phase conversion to obtain the antibacterial film. In the gel bath, the hydrophilic additives and solvent molecules quickly detach from the homogeneous casting solution and diffuse into the water phase, forming a certain pore structure on the membrane section and surface, thereby affecting the flux and interception performance of the membrane.

[0037] In some embodiments, the gel bath is one or more of pure water, 5%-10% propanol solution, and 2%-10% ethanol solution.

[0038] In some embodiments, the base membrane material is one or more of polyethersulfone, polysulfone, polyvinylidene fluoride, cellulose acetate, polyamide, and chitosan.

[0039] One of the preparation processes is as follows:

[0040] m-SiO 2 -SH preparation: Mix 2.1mL (2M) NaOH with 288mL distilled water, add 0.6g CTAB (hexadecyltrimethylammonium bromide), heat and stir to 80°C, then add 3mL tetraethyl orthosilicate and stir for 2 hours. Let stand for aging for 3 hours, wash and dry. The dried powder was refluxed in 150mL ethanol and 2mL hydrochloric acid for 12 hours, refluxed several times to completely remove the template, washed and dried to obtain mesoporous silica solid powder (m-SiO 2 ). 0.5 g of powdered m-SiO 2 Ultrasonic dispersion was performed in 100 mL of ethanol solution, 1 mL of 3-mercaptopropyltrimethoxysilane was added, and refluxed at 70°C for 12 h under a magnetic stirrer. After cooling, the mixture was repeatedly washed with ethanol and deionized water, and dried and ground at 60°C.

[0041] The thiol-modified mesoporous silica (m-SiO 2 -SH) sulfonation process includes: 0.5g m-SiO 2 -SH powder was dispersed in chlorosulfonic acid (ClSO 3 H, 0.1 mol / L) 100 mL solution, magnetically stirred at room temperature for 24 hours, repeatedly washed with ethanol and deionized water, dried at 60 °C and ground into powder.

[0042] m-SiO 2 -SH-Ag preparation: 1 mg / mL mesoporous silica (m-SiO 2 -SH) was dispersed in water and ultrasonicated, and 0.01-0.03 mol / L silver nitrate AgNO was added 3 , stirred overnight in the dark, and the solid was washed and freeze-dried to obtain m-SiO 2 -SH-Ag.

[0043] HA coating:

[0044] First, hyaluronic acid-sodium catechol (HA) compound was synthesized by amide reaction. 0.5g sodium hyaluronate, 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) were added to 60mL PBS. After stirring for 1h, 0.5g dopamine was added and the reaction continued overnight. The product was dialyzed and freeze-dried and stored at -20℃.

[0045] 0.1 mg / mL HA and 2 mg / mL m-SiO 2 -SH-Ag mixture was stirred for 4 h at room temperature in the dark. 2 -SH-Ag-HA complex.

[0046] The silicon dioxide with mesoporous structure in the above embodiment can also be commercial silicon dioxide powder (surface area of ​​1000m 2 / g, BET; MCM-41type (hexagonal); Product Number: 643645; from Sigma-Aldrich).

[0047] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0048] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

Claims

1. A method for preparing an antibacterial film, characterized in that: include: Preparation and formation of m-SiO2-SH-Ag-HA composite material; The m-SiO2-SH-Ag-HA composite material is blended into a membrane material to form the antibacterial membrane.

2. The method according to claim 1, characterized in that: The preparation method for forming the m-SiO2-SH-Ag-HA composite material comprises: The -SH thiol-modified m-SiO2 is sulfonated with chlorosulfonic acid (ClSO3H) and then dispersed in water to form an m-SiO2-SH solution. AgNO3 solution is added to the m-SiO2-SH solution to form a first mixed solution. The first mixed solution is centrifuged and washed to obtain a m-SiO2-SH-Ag solid; the m-SiO2-SH-Ag solid is dispersed in water, and a sodium hyaluronate-catechol (HA) compound is added to form a second mixed solution. The second mixed solution is stirred at room temperature and in the dark, and is centrifuged, washed and dried to form a m-SiO2-SH-Ag-HA composite material.

3. The method according to claim 2, characterized in that: The step of adding AgNO3 solution to the m-SiO2-SH solution to form the first mixed solution comprises: adding AgNO3 solution to the m-SiO2-SH solution, mixing the solution and subjecting the solution to magnetic stirring in the dark for a first preset time to form the first mixed solution.

4. The method according to claim 2, characterized in that: The preparation method of the sodium hyaluronate-catechol (HA) compound comprises: adding sodium hyaluronate, 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and NHS (N-hydroxysuccinimide) into PBS, stirring for 1 hour, supplementing dopamine, reacting overnight, and dialyzing and freeze-drying the product to obtain the sodium hyaluronate-catechol (HA) compound.

5. The method according to claim 2, characterized in that: The preparation method of the thiol-modified mesoporous silica (m-SiO2-SH) comprises: adding CTAB (hexadecyltrimethylammonium bromide) to a sodium hydroxide solution, heating and stirring to 80°C, then adding 3 mL of tetraethyl orthosilicate, stirring for 2 hours, standing and aging for 3 hours, and then washing and drying; refluxing the dried powder in 150 mL of ethanol and 2 mL of hydrochloric acid for 12 hours, washing and drying to obtain the m-SiO2, ultrasonically dispersing the powdered m-SiO2 in an ethanol solution, adding 3-mercaptopropyltrimethoxysilane, refluxing at 70°C for 12 hours under a magnetic stirrer, cooling and repeatedly washing with ethanol and deionized water, and drying and grinding at 60°C.

6. The method according to claim 2, characterized in that: The sulfonation treatment process of the thiol-modified mesoporous silica (m-SiO2-SH) comprises: dispersing the m-SiO2-SH powder in a chlorosulfonic acid (ClSO3H, 0.1 mol / L) solution, magnetically stirring at room temperature for 24 hours, repeatedly washing with ethanol and deionized water, drying at 60°C and grinding into powder.

7. The method according to claim 1, characterized in that: The m-SiO2-SH-Ag-HA composite material is blended into a membrane material to form the antibacterial membrane, comprising: The m-SiO2-SH-Ag-HA composite material is added to an organic solvent and stirred to make it evenly dispersed, and then a preset amount of base film material is added to form a second mixed liquid, the second mixed liquid is placed in an oven and heated to 50-80°C to dissolve, and the heated and dissolved second mixed liquid is placed on a magnetic stirrer and stirred overnight; the stirred second mixed liquid is placed in an oven and allowed to stand for 24 hours to obtain a casting liquid, the casting liquid is naturally allowed to stand and wait for it to cool to room temperature, the cooled casting liquid is poured on a non-woven fabric, and it is evenly scraped with a glass rod, and then the glass plate covered with the non-woven fabric is immersed in a gel bath, and it is solidified to form a film of uniform thickness, and the film is continuously immersed for 24 hours to complete the phase conversion to obtain the antibacterial film.

8. The method according to claim 6, characterized in that: The gel bath is one or more of pure water, 5%-10% propanol solution, and 2%-10% ethanol solution.

9. The method according to claim 7, characterized in that: The base membrane material is one or more of polyethersulfone, polysulfone, polyvinylidene fluoride, cellulose acetate, polyamide, and chitosan.

Citation Information

Cited By

  • Method and application of hydroxyapatite and silver composite coating modified antibacterial film

    CN119800309A

  • Composite permeable membrane for water desalination and preparation method thereof

    CN120733577A

  • Composite permeation membrane for water desalination and method for preparing the same

    CN120733577B